Toxicological characterization of supported ionic liquids for the removal of non-steroidal anti-inflammatory drugs from aqueous solutions - Valente, João Vasco (2022)
Non-steroidal anti-inflammatory drugs (NSAIDs) are a class of widely used pharmaceuticals that has been detected in the aquatic environment. Due to their deleterious environmental and health concerns associated with “boomerang” effect, several technologies have been proposed to prevent their release into the environment. In this work, new ionic liquid-based materials were used to remove NSAIDs from aqueous solutions and their potential cytotoxicity and in vivo toxicity was evaluated towards two human cell lines (Caco-2 and HepG2) and the model organism Daphnia magna. The obtained results disclose that the studied materials exhibit low cytotoxic potential with decreases in cell viability lower than 10% for Caco-2 and 30% for HepG2, and no acute toxicity towards D. magna. These promising results open the possibility of application of ionic liquid based materials in the treatment of aqueous media such as effluents and even drinking water.